ADAPTATION OF FOREIGN TEACHER IN THE PROCESS OF LEARNING IN DARMA YUDHA HIGHSCHOOL PEKANBARU - Ramadhani, Futry; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Education in indonesia is growing. Neither the national school, or international schools are competing to provide best quality. When the foreign teachers having a new culture, then the teachers should do adaptation process both in terms of teaching and learning environment in their daylife. This study aims to determine the stages of the adaptations made by foreign teachers, and what are the barriers that they face when adapting to the new environment. This study used a qualitative research method with a descriptive approach, which gives an overview of the situation and analyze the data based on the field survey. The data source consists of primary data and secondary data. Collecting data using interviews, documentation and field observations. Informants were obtained by 3 people based sampling with purposive sampling technique. The subject of this research is foreign teachers who teach in Dharma Yudha high school and the object of this study is the cultural adaptation of foreign teachers in teaching and learning in Dharma Yudha high school. The results of this study indicate that the three foreign teachers have different process of adaptation, two of the informants were in the stage of resolution with the decision that accepts cultural accommodation but with several notes about things they can not tolerate and one informant another at the stage resolution with a full participant in the decision that is, someone who reached a comfortable and managed to establish a good relationship with the surrounding environment and accept the new culture. Keywords: culture, adaptation, foreign teacher, experience